Use of healthcare services during the COVID-19 pandemic in urban Ethiopia: evidence from retrospective health facility survey data - Getnet Alemu; Arjun S Bedi; Zemzem Shuka; Anagaw Mebratie; Matthias Rieger (BMJ Open)
Objectives In recent years, Ethiopia has made enormous strides in enhancing access to healthcare, especially, maternal and child healthcare. With the onset and spread of COVID-19, the attention of the healthcare system has pivoted to handling the disease, potentially at the cost of other healthcare needs. This paper explores whether this shift has come at the cost of non-Covid related healthcare, especially the use of maternal and child health (MCH) services.Setting Data covering a 24-month period are drawn from 59 health centres and 29 public hospitals located in urban Ethiopia.Primary and secondary outcomes measures The primary outcome measures are the use of MCH services including family planning, antenatal and postnatal care, abortion care, delivery and immunisation. The secondary outcome measures are the use of health services by adults including antiretroviral therapy (ART), tuberculosis (TB) and leprosy and dental servicesResults There is a sharp reduction in the use of both inpatient (20%–27%, p<0.001) and outpatient (27%–34%, p<0.001) care, particularly in Addis Ababa, which has been most acutely affected by the virus. This decline does not come at the cost of MCH services. The use of several MCH components (skilled birth attendant deliveries, immunisation, postnatal care) remains unaffected throughout the period while others (family planning services, antenatal care) experience a decline (8%–17%) in the immediate aftermath but recover soon after.Conclusion Concerns about the crowding out of MCH services due to the focus on COVID-19 are unfounded. Proactive measures taken by the government and healthcare facilities to ring-fence the use of essential healthcare services have mitigated service disruptions. The results underline the resilience and agility displayed by one of the world’s most resource-constrained healthcare systems. Further research on the approaches used to mitigate disruptions is needed.